1967
DOI: 10.1507/endocrj1954.14.39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycyrrhizin on Thymolytic and Immunosuppressive Action of Cortisone

Abstract: SYNOPSISGlycyrrhizin has been clinically used as an anti-allergic agent, but its mechanism remains unknown. This study was undertaken to examine the effect of glycyrrhizin on thymolytic and immunosuppressive action of cortisone in normal rabbits and adrenalectomized rats. Immunization was performed by injection of bacterial a-amylase emulsified in Freund's incomplete adjuvant. Antibody titer of the serum was expressed as the enzyme-neutralizing activity. The circulating antibody could be detected in normal rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…21 An animal study has shown that glycyrrhizin prevented the immune-suppressing actions of cortisone. 32 Although corticosteroids have been reported to show interactions with licorice, there is no published study examining the prevalence and frequency of concurrent use of corticosteroids with licorice-containing TCM preparations among the Taiwanese.…”
Section: Introductionmentioning
confidence: 99%
“…21 An animal study has shown that glycyrrhizin prevented the immune-suppressing actions of cortisone. 32 Although corticosteroids have been reported to show interactions with licorice, there is no published study examining the prevalence and frequency of concurrent use of corticosteroids with licorice-containing TCM preparations among the Taiwanese.…”
Section: Introductionmentioning
confidence: 99%
“…Liquiritigenin and isoliquiritigenin from G. uralensis have some valuable pharmacological activities. Glycyrrhiza uralensis has been proven to exhibit naturally occurring anti-allergic effects (Kumagai, Nanabosh, Asanuma, Yagur, & Nishino, 1967) and has also shown growth inhibitory effect on cancer cells (Kanazawa et al, 2003). Moreover, it also exhibited an anti-angiogenic effect (Kobayashi, Miyamoto, I. Kimura, & M. Kimura, 1995) and antioxidant activities (Lee, Hwang, Ha, Jeong, & Kim, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin and glycyrrhetinic acid, derived from licorice (Glycyrrhizia glabra), bind to glucocorticoid receptors and exert anti-inflammatory effects.1 In addition, licorice extracts also induce inferieron production and inhibit the growth of many DNA and RNA viruses. [13][14][15] Lobelia Lobelia (Lobelia inflata) is an effective expectorant with a proposed mechanism of action that arises from adrenal-gland stimulation, which results in bronchial smoothmuscle relaxation.16'17 This herb has also been used to help in achieving smoking cessation and may actually decrease the classical smoker's cough via another mechanism.…”
Section: Glyceryl Guaiacolatementioning
confidence: 99%